Diary of Mick Dwyer - Dwyer, Michael Ignatius (1931)
Diary written by Mick Dwyer who accompanied Michael Leahy on his trip across New Guinea, April to November 1931.
Manuscript reference no. : MS 6298.
Keywords: Dwyer, Michael Ignatius -- Diaries; Leahy, Michael J., -- 1901-1979.; Explorers -- New Guinea -- Diaries; New Guinea -- Discovery and exploration; Explorers